COMPARATIVE STUDY ABOUT THE OPINION OF PHYSICAL EDUCATION GRADUATE AND UNDERGRADUATE STUDENTS FROM THE UNIVERSITY OF BRASÍLIA, CONCERNING THE FIELD FOR PROFESSIONAL WORK: EXPECTATIONS AND EXPERIENCES. (Fiep Bulletin - online, 2014)
ABSTRACT The present work deals with the evaluation of the conditions which surround the professional work of Physical Education teachers. The comparison between the opinion of graduate and undergraduate students allows us to verify whether their expectations were fulfilled, redeveloped and/or amplified, providing important data for the evaluation of their professional life. The main conclusions point out to: 1) the awareness of the difficulties of the profession recognition and valorization; 2) the confirmation of the usual view, in which the Physical Education teacher likes what he does and finds it pleasurable; 3) the certainty that the course qualifies for the work as an educator; 4) a warning that work conditions and income are worse than undergraduates expect.
Keywords: Physical Education; curriculum; professional formation